The Role of Compensation in Improving Work Performance of Mattampa Bulu Village Officials, Lamuru District, Bone Regency - Irmawati Irmawati; Syahidah Rahmah; M. Awaluddin; Hezron Alhim Dos Santos; Feby Triadi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
Compensation is one of the important components in Village Governance. This study aims to determine the role of compensation in improving the work performance of village officials in Mattampa Bulu Village, Lamuru District, Bone Regency. The type of research used is descriptive qualitative research. The research subjects to be investigated were all seven Mattampa Bulu Village officials. The object of the research studied was how big the role of compensation was in improving the work performance of the Mattampa Bulu Village apparatus, Lamuru District, Bone Regency. Determination of informants in this study using purposive techniques, namely techniques that are based on certain considerations from the researcher. The research data were obtained from various sources, namely: primary data and secondary data using data collection techniques, namely: interview techniques, observation techniques, and documentation techniques. This research was conducted with a qualitative interactive model from Miles, Huberman, namely: data condensation, data display, and conclusion drawing/verification. Based on the results of the research for all of the above aspects ranging from salaries, initiatives, and health and fitness benefits, it can generally be concluded that the role of compensation in improving the work performance of the Mattampa Bulu village apparatus, Lamuru District, Bone Regency is considered to be running well.